PAIN MANAGEMENT IN BURN INJURY - Jaya, A A Gde Putra Semara; Anggreni, Anak Agung Ayu; Senapathi, Tjokorda Gde Agung (DiscoverSys Inc., 2018)
Burn injury is one of the challenging cases in medical practice, which need comprehensive and multidiscipline management. Pain management is one of an important factors in caring for the burn patient. Pain management in burn injury is challenging and the patient may be at risk for undertreatment. Undertreated severe acute pain can lead to adverse consequences of many organ systems, delay recovery and discharge process, and potentially lead to chronic pain. Reports of inadequate pain relief persist, although there are advances in the acute pain management in recent years.An understanding of pain pathway can achieve effective burn injury pain management, types of pain in burn injury, analgesics selection, continuous and accurate assessment of the pain and the response to therapy, dose adjustment to achieve maximum effect and minimal side effect, and role of nonpharmacological treatment as a complement to medication. Acute pain service plays an important role in providing effective burn injury pain management for reducing morbidity and mortality.